Regioselectivity of Larock heteroannulation: A contribution from electronic properties of diarylacetylenes - Nared Phetrak (2018)
A series of 2,3-diarylindoles were synthesized from 2-iodoaniline and unsymmetrical diarylacetylenes using the Larock heteroannulation. Diarylacetylenes bearing electron-withdrawing substituents lead to 2,3-diarylindoles with substituted phenyl moieties at the 2-position as major products, while those with electron-donating groups preferably yield indole products with substituted phenyl moieties at the 3-position. The regioisomeric product ratios exhibit a clear correlation with Hammett σp values. DFT calculations reveal the origin of this effect, displaying smaller activation energy barriers for those pathways leading to the major regioisomer. © 2013 American Chemical Society.